(untitled) (Journal of Global Arts Studies, 2025)
Background: Teaching quality evaluation in art education faces unique challenges because of its inherent subjectivity and multidimensional characteristics. Objective: This study proposes an integrated evaluation approach combining the Analytic Hierarchy Process (AHP) and the fuzzy comprehensive evaluation method to assess the quality of art teaching in higher education. Methods: Data were collected from 300 undergraduate students across three academic years through structured questionnaires. The evaluation framework included four primary dimensions: teaching content, teaching methods, teaching attitude, and teaching effects. Results: The results revealed an overall teaching quality membership degree of 0.2322, with teaching content (weight = 0.36) and teaching methods (weight = 0.26) identified as the most influential factors. Teaching attitude (weight = 0.27, membership degree = 0.18) and teaching effects (weight = 0.11, membership degree = 0.16) demonstrated considerable potential for improvement. Conclusion: The findings indicate that the integrated approach provides a more systematic and objective mechanism for evaluating art teaching quality, offering practical insights for teaching improvement and curriculum development. This study contributes to the methodological advancement of teaching quality assessment in art education and provides practical implications for educational administrators and policymakers.